A = 10 MŨ 1990 + 1 / 10 MŨ 1991 + 1 VÀ B = 10 MŨ 1991 + 1 / 10 MŨ 1992 + 1 GIẢI GIÚP MÌNH MỘT CÁCH DỄ HIỂU

A = 10 MŨ 1990 + 1 / 10 MŨ 1991 + 1 VÀ B = 10 MŨ 1991 + 1 / 10 MŨ 1992 + 1
GIẢI GIÚP MÌNH MỘT CÁCH DỄ HIỂU

2 bình luận về “A = 10 MŨ 1990 + 1 / 10 MŨ 1991 + 1 VÀ B = 10 MŨ 1991 + 1 / 10 MŨ 1992 + 1 GIẢI GIÚP MÌNH MỘT CÁCH DỄ HIỂU”

  1. Ta có: A = (10^(1990) + 1)/(10^(1991) + 1)
    => 10A = (10^(1991) + 10)/(10^(1991) + 1)
    => 10A = (10^(1991) + 1 + 9)/(10^(1991) + 1)
    => 10A = 1 + 9/(10^(1991) + 1)
    Lại có: B = (10^(1991) + 1)/(10^(1992) + 1)
    => 10B = (10^(1992) +10)/(10^(1992) + 1)
    => 10B = (10^(1992) + 1+ 9)/(10^(1992) + 1)
    => 10B = 1 + 9/(10^(1992) + 1)
    Vì 10^(1991) < 10^(1992)
    => 10^(1991) +1 < 10^(1992) + 1
    => 1/(10^(1991) + 1) > 1/(10^(1992) + 1)
    => 9/(10^(1991) + 1) > 9/(10^(1992) + 1)
    => 1 + 9/(10^(1991) + 1) > 1 + 9/(10^(1992) + 1)
    => 10A > 10B
    => A  >B
    Vậy A > B

    Trả lời

Viết một bình luận

Câu hỏi mới